Thermolabile drugs: pharmacist intevention as a guarantee of cold chain maintenance - I. Ricote-Lobera; B. Santos-Mena; S. Fraile-Gil; B. Ortiz-Martín; F. J. Hidalgo-Correas; B. García-Díaz (Elsevier, 2014)
Objective: To determine whether pharmacist is able to guaranteecold chain maintenance of thermolabile drugs during transportusing the available information in the reception processand to compare these results with those obtained in a subsequentintervention phase, in which the manufacturing laboratorieswere contacted. Methods: Intervention study, prospective and comparative"before-after". It was analyzed the storage conditions duringtransport of all thermolabile drugs received in a 400-bed hospitalfor 3 months, excluding those from clinical trials. Results: The intervention allowed to ensure cold chain maintenancein 76,5% (n = 488) of received drugs, representing anincrease of 41,8% (IC 95% 36,7-46,6%; p < 0,001) comparedwith the percentage obtained before the intervention. Conclusions: The pharmacist isn't able to ensure the cold chainmaintenance of received thermolabile drugs without temperaturemonitoring device (64,6%). Reports requested from laboratoriesallowed to increase significantly that percentage.